The Effect of PEEP Adjusted by Automatic Recruitment Maneuver on Total and Dynamic Mechanical Power in Bariatric Surgery - (:unkn) unknown (GALENOS YAYINCILIK, 2021)
Objective: Mechanical power is a predictor of ventilator-induced lung damage. An automatic recruitment maneuver (ARM) is used during anesthesia to adjust the optimal positive end-expiratory pressure (PEEP) level. This study compared the total mechanical and dynamic power of patients who underwent sleeve gastrectomy due to morbid obesity who are ventilated with PEEP adjusted according to the anesthesiologists' decision and those adjusted using ARM. Methods: Patients between the ages of 18 and 65 years, with American Society of Anesthesiologists (ASA) III and body mass index of >40, were divided into two groups: group 1 with PEEP adjusted using the ARM and group 2 without the ARM. Total mechanical power and dynamic power in both groups were calculated using respiratory mechanics measured at 10-min intervals. Patient averages of the calculated power values of both groups were compared with the Mann-Whitney U test. Results: Simplified mechanical power of pressure control ventilation (MPpcv(simpl)) (dynamic) resulted 2.9 (2.4-3.4) in group 1 and 7.9 (6.4-9.6) in group 2 (p<0,0001). MPpcv(simpl) (total power) resulted 8.1 (7.4-8.9) in group 1 and 12.8 (9.9-15.2) in group 2 (p<0.0001). Conclusion: Optimal PEEP adjustment by ARM reduced the lung elastance and DP, resulting in less dynamic power applied to the respiratory system.
Keywords: Obesity; mechanical power; PEEP; recruitment maneuver; LUNG INJURY; VENTILATION; PRESSURE